Biomechanical analysis of the drilling parameters for early osteonecrosis of the femoral head. (June 2022) - Yuan, DaiZhu; Wu, ZhanYu; Yang, Long; Zou, Qiang; Hua, DaWei; Zou, ZiHao; Ye, Chuan
Highlights: Postoperative biomechanical properties of different drilling parameters. Stress changes of the osteonecrosis of the femoral head under slow running loads. Slow running can be permitted depending on different locations and diameters. The range of safety drilling parameters to avoid the postoperative complications. Abstract: Background and objective: Core decompression is a surgical procedure commonly used to treat the early osteonecrosis of the femoral head. However, It is not known whether different drilling parameters affect postoperative biomechanical strength. This study aimed to analyze the mechanical stability of different drilling locations and diameters of core decompression using finite element analysis. Methods: Finite element models were established based on computed tomography images obtained from five healthy participants, including the different drilling locations (Lesser trochanter: Above, Parallel, and Below) and diameters. Biomechanical parameters including stiffness and stress were evaluated under slow running loads. Results: At the same drilling diameter, the femoral stiffness was highest ( p < 0.05) in the Above group and lowest in the Below group, while the maximum equivalent stress of the entry area and the necrotic area was highest ( p < 0.05) in the Below group and lowest in the Above group. With the increase of drilling diameters, the stiffness decreased and its decreased percentage comparing the preoperative: Above (1.06–8.82%), Parallel (2.51–13.61%), and Below (3.99–15.06%). The maximum equivalent stress of the entry area and necrotic area increased as the drilling diameter increased, and its increased percentage comparing the preoperative, for the entry area: Above (14.11–219.58%), Parallel (35.91–306.37%), and Below (46.12–240.98%); for the necrotic area: Above (13.64–114.69%), Parallel (29.37–187.76%), and Below (44.76–202.10%). The range of safety drilling parameters (SDP) was obtained (Below<9 mm, Parallel<11 mm, and Above<13 mm) by comparing the maximum equivalent stress of two areas and its yield strength. For patients of different sizes and normal bone mineral density (BMD), the maximum equivalent stress of the two areas did not exceed its yield strength using the range of SDP, except for the patients with abnormal BMD (Osteoporosis) or high body mass index (BMI≥28 kg/m 2 ). Conclusions: The biomechanical properties of early osteonecrosis of the femoral head deceased with increasing drilling diameters parameters, especially at the location below the lesser trochanter. The SDP (Below<9 mm, Parallel<11 mm, and Above<13 mm) is a suitable reference for most patients to perform slow running postoperatively, while it may be not suitable for patients with osteoporosis or obesity.